UV-curable palm oil based-urethane acrylate/clay nanocomposites - M. Salih, Ashraf; Wan Yunus, Wan Md Zin; Mohd Dahlan, Khairul Zaman; Mahmood, Mohd Hilmi; Ahmad, Mansor (Universiti Putra Malaysia Press, 2012)
Synthesis of palm oil based-urethane acrylate (POBUA) resins was carried out by acrylation of epoxidized palm oil (EPOP) using acrylic acid in the presence of a catalyst and followed by isocyanation to obtain the POBUA. Using the monomer as a diluent in the formulation, 4% of photoinitiator and incorporation of organoclay (1-5% wt), nanocomposites were obtained upon UV irradiation. The X-ray Diffractory XRD study revealed that the nanocomposites obtained were of the exfoliation type. The presence of the clay improved the hardness and did not affect the thermal stability. Similarly, it increased the glass transition temperature Tg but reduced the modulus as the clay content was increased. The improvement of the tensile strength was only obtained when the clay concentration was 5 phr.